2016
DOI: 10.14238/sp12.2.2010.128-34
|View full text |Cite
|
Sign up to set email alerts
|

Luaran Pengobatan Fase Induksi Pasien Leukemia Limfoblastik Akut pada Anak di Rumah Sakit Umum Dr. Soetomo Surabaya

Abstract: Kata kunci: leukemia limfoblastik akut, aspirasi sumsum tulang, anak, fase induksi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
1
Order By: Relevance
“…A similar study in Surabaya, East Java, stated that patients aged 2 -5 years had 2 times higher survival rate than those aged <2 years and >10 years. 3 Age at diagnosis was a significant prognostic factor, despite differences in immunophenotype and morphology. Almost 80% of patients under 1 year with ALL had a mixed-lineage leukemia gene accompanied by higher leukocyte counts and risk for CNS leukemia, which leads to lower survival rate under 1 year group.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A similar study in Surabaya, East Java, stated that patients aged 2 -5 years had 2 times higher survival rate than those aged <2 years and >10 years. 3 Age at diagnosis was a significant prognostic factor, despite differences in immunophenotype and morphology. Almost 80% of patients under 1 year with ALL had a mixed-lineage leukemia gene accompanied by higher leukocyte counts and risk for CNS leukemia, which leads to lower survival rate under 1 year group.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, other studies in Surabaya (East Java) and in Vietnam reported that cause of death was infection related, with 76% and 43.2% respectively. 3,14 Cox multivariate regression revealed that high risk status had significantly increased risk of death by 3 times (HR=3.0; 95%CI 1.9 to 4.9), and the ALL-2006 group had significantly lower risk by 0.3 times compared to the ALL-2013 group (HR=0.3; 95%CI 0.12 to 0.9). Similarly, a study in Yogyakarta (Central Java) found that even though leukocyte counts and age were statistically significant in univariate analysis, they were not significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kejadian pada penelitian ini ditemukan bahwa usia yang paling banyak menjalani kemoterapi pada usia 5-10 tahun, hal ini dikarenakan populasi dalam satu terakhir menunjukkan bahwa usia penderita. Hal ini berbeda dengan Permono, & Ratwita (2016) yang mengatakan bahwa puncak insiden leukemia terjadi pada anak dengan usia antara 2 sampai 5 tahun.…”
Section: Pembahasanunclassified